Migration and (Im)Mobility Biographical Experiences of Polish Migrants in Germany and Canada (Edition 1) - Wieczorek, Anna Xymena (transcript Verlag, 2018)
In her endeavour to overcome the established methodological, conceptual, and empirical dualism of mobility and migration, Anna Xymena Wieczorek develops a "mobilities perspective" by combining migration studies theories with approaches of the mobility studies. With the help of rich empirical data gathered among young adults of Polish heritage in Germany and Canada, Wieczorek conceptualizes three patterns of (im)mobility which illustrate the diversity of immigrants' geographical movements after their initial migration. She thus reveals the different social configurations promoting or hindering the development, maintenance or shifting of each pattern in migrants' biographical trajectories.